Communities of Practice and the Buddhist Education Reforms of Early-Twentieth-Century China - Boros, Peter (Approaching Religion, 2024)
Over the course of only a few decades during the late nineteenth to early twentieth centuries, part of mainstream Buddhist education underwent a striking shift in China. From being a secluded practice within monastery walls taught by monastics for monastics with a strict focus on Buddhist scripture, it became one where monastics and laypeople study together, guided by teachers, both monastic and lay, studying a curriculum of both Buddhist and secular subjects. Although general reforms within the Buddhist community of the times received considerable scholarly attention, the topic of education development was discussed in only a few instances. Therefore, the present article sets out to explore why this radical methodological shift happened, and more concretely, how the individual learning trajectories of the reforms’ leading actors, and their involvement in specific communities, influenced the way the reforms unfolded. The author analyses the work and life of three generations of Buddhist reformers, namely the layman Yang Wenhui, and the monastic masters Taixu, Hsing Yun and Cheng Yen, employing Étienne Wenger’s social theory of learning. The theory’s main assertion that communities of practice provide the main fora of learning for individuals, and its description of the concrete ways in which this learning takes place can provide new insights regarding the specific unfolding of late-nineteenth to early-twentieth-century Buddhist education reforms in China.